An Investigation on Polymerization of Ethylene by Ziegler-Natta Catalyst in the Presence of a Promoter: Polymerization Behavior and Polymer Microstructure - Yaghoob Gholami; Majid Abdouss; Sadegh Abedi; Farhad Azadi; Pezhman Baniani; Maryam Arsalanfar (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
The effect of a halocarbon (ethyl chloride) as a promoter on a Ziegler-Natta catalyst composed of‌ T‌iCl4 (catalyst), AlEt3 (activator) and Mg(OEt)2 (support) in the polymerization of ethylene have been investigated. In addition, the impact of this compound on the structural and thermal properties of the produced polyethylene has been studied. The catalyst activity and polymerization rate increased almost up to twice when a suitable molar ratio of ethyl chloride to triethylaluminum (TEA) was used. There was no change in the type of the profile of the polymerization rate during the polymerization time. A reduction in the polymer molecular weight was observed in the presence of the promoter and hydrogen. In addition, the MWD curve shifted toward lower values in the presence of ethyl chloride. Furthermore, a numerical method was used to obtain the most probable chain-length distribution, number average molecular weight and weight fraction corresponding to each site type in the presence and absence of the promoter. Since, the catalyst had an irregular shape, the produced polymer also showed a similar morphology. In addition, the promoter used in the polymerization did not have any effect on the produced polymer morphology. The DSC results indicated that the presence of the promoter in the polymerization led to a decrease in the melting point of the produced polymer; whereas, there were no remarkable changes in the crystallization temperature of the polymers.